Pre-clinical in vivo evaluation of Malaysian-made “osteopaste” – an injectable self-hardened synthetic bone cement in critical size bone defects - Mohamed Amin, Mohamed Azril; Che Seman, Che Nor Zarida; Zakaria@Mohamad, Zamzuri; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Che Ahmad, Aminudin; Buyong, Zunariah; Fazan, Fazilah (2015)
Osteopaste is a locally produced synthetic bone graft. It is produced from limestone that has been converted to a combination of tetra-calcium phosphate (TTCP) and tri-calcium phosphate (TCP) powders simultaneously. In this study, pre-clinical evaluations (in vivo) of critical size defect (CSD) in New Zealand White rabbit has been conducted to evaluate the effectiveness of Osteopaste. This injectable Osteopaste is hoped to have an edge to be used as bone graft substitutes to enhance repair of critical size bone defects.